Preconceito e discriminação contra pessoas transgênero: o papel da ameaça à distintividade de gênero - Lima, Kaline da Silva (2022)
Negative attitudes and discrimination against transgender people are widespread in Brazil. However, little attention has been paid to the specificity of transphobic prejudice and the role of threats to gender distinctness in discriminatory attitudes towards these people. To address this question, we developed a research programme in which we conducted eight studies, which we present in three empirical articles. In the first article, we present four preliminary studies in which we describe the development and validation of a scale of prejudice against women (PTS -W) and transgender men (PTS -M). The results showed consistent empirical evidence for the construct validity and reliability of PTS -M and PTS -W. In the second article (N = 300), we conducted an experimental study examining the specificity of discrimination against transgender people expressed in the social value people attribute to transgender people who are victims of injustice. We manipulated the victim's sex reported at birth (male vs. female) and information about their categorical membership (heterosexual vs. homosexual vs. transgender). The results showed that a heterosexual victim was rated more highly than a transgender victim. Article 3 describes three experimental studies that test the hypothesis that discrimination against transgender people is stronger among men than women and that this difference is due to threats to gender distinctiveness and transphobic prejudice. In Study 1 (N = 162), we manipulated the victim's sex determined at birth (female vs. male) and gender identity (cisgender vs. transgender) and measured the social support the victim received. Male participants expressed less social support for the transgender victim, and this effect was mediated by transphobic prejudice. In Study 2 (N = 196), we manipulated threat to gender distinctiveness using a fictional news story that highlighted the similarity (i.e., threat to distinctiveness) between cisgender and transgender people and a control condition (i.e., neutral news). Results indicated that perceptions of gender difference and prejudice against transgender people sequentially mediated the relationship between participants' gender and lower social support for the transgender victim, particularly in the gender difference threat condition. In Study 3 (N = 350), we manipulated gender distinctiveness threat through false feedback describing the similarity (i.e., distinctiveness threat) or difference (i.e., distinctiveness assertion) between cisgender participants' (vs. transgender) personalities. Cisgender men who perceived greater distinctiveness from transgender people expressed more prejudice and offered less social support to trans people than cisgender people, especially in the condition of affirming gender distinctiveness. Overall, the results are consistent with our hypotheses and the observed inconsistencies were discussed based on social identity theory, highlighting the role of threats to intergroup distinctiveness.